2017
DOI: 10.1111/eje.12268
|View full text |Cite
|
Sign up to set email alerts
|

Are dental students ready for supercomplex dental practice?

Abstract: Contemporary dental practice requires practitioners who are able to draw upon varying interconnected knowledge and skills, in order to make judgments and take action when faced with multiple, often contradictory, ways of interpreting a situation. However, the curricula that prepare students for dental practice are traditionally based on the theoretical knowledge and technical skills to be gained by students. This is despite evidence in the dental literature of a collective desire for graduates to have more ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 52 publications
0
15
0
3
Order By: Relevance
“…The semistructured nature of the interviews allows for the participants to discuss the same phenomenon and to illuminate their experiences through examples that came to mind, but at the same time to pursue angles of understanding that were exposed through the participant responses. The primary questions were derived from aspects of the dental curriculum that have recently been the subject of research, or identified as areas for further research . Table lists the primary and follow‐on interview questions and examples of probing questions.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The semistructured nature of the interviews allows for the participants to discuss the same phenomenon and to illuminate their experiences through examples that came to mind, but at the same time to pursue angles of understanding that were exposed through the participant responses. The primary questions were derived from aspects of the dental curriculum that have recently been the subject of research, or identified as areas for further research . Table lists the primary and follow‐on interview questions and examples of probing questions.…”
Section: Methodsmentioning
confidence: 99%
“…The primary questions were derived from aspects of the dental curriculum that have recently been the subject of research, or identified as areas for further research. 2,[12][13][14][15][16][17]20 Table 1 lists the primary and follow-on interview questions and examples of probing questions. Interviews lasted between 35 and 60 minutes, were audio-recorded and verbatim transcripts were produced for analysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the curriculum could be improved by employing additional training. 12 However, the cost-effectiveness of conducting such additional training should also be investigated to support employing this type of educational strategy. In addition, the conduction of a multicentre study to test the applicability of this kind of methodology in other centres and realities seems to be interesting for future perspectives.…”
Section: Ta B L E 2 (Continued)mentioning
confidence: 99%
“…Thus, the book has paved the way for a large host of philosophers of education (Bengtsen & Barnett, in press) who have taken on the more specific aim of conducting philosophy of Higher Education—an aim Barnett has indeed been the main driver of promoting and qualifying during his authorship in the two decades following the publication of the book. Today, the book keeps inspiring new readers (e.g., Leadbeatter & Peck, ; Niekerk, ; Yuen, ) with its stylistic power and conceptual rigour. My own chief aim with this article is to revitalise and reinvigorate the philosophical and social discussions on the university by drawing out Barnett's call for more focus on Higher Education teaching and learning practices as spaces for existential transformation and social agency.…”
Section: Introductionmentioning
confidence: 99%